DEVELOPMENT OF BIODEGRADABLE LUBRICATING OIL FOR TURBINE BEARING FROM PALM KERNEL AND CASTOR OILS - Ibrahim, Aminu O.; Ali, Ademoh N.; Albert, Lawal S.; Oyewole, Adedipe; Abdullahi, Aliyu A.; Abdulsalam, Aliyu O.; Michael, Ohakwere-Eze C. (FUDMA JOURNAL OF SCIENCES, 2025)
The search for sustainable and environmentally friendly alternatives to conventional mineral-based oil lubricants has led to increasing research into bio-based lubricants for industrial applications. This study develops biodegradable lubricating oil for turbine bearing from palm kernel and castor oils through chemical modification and additive blending. Using transesterification method, the oils were converted to their various methyl esters and blended with additives such as ethylene glycol, ascorbic acid, trimethylopropane, and graphene. Physiochemical evaluations of both palm kernel and castor developed lubricating oils showed improved viscosity, pour point, thermal stability, neutralization number, and flash point against their natural oils. While their tribological evaluation revealed that among the developed samples, Palm kernel oil-based turbine lubricant 1 (PKOTL1) exhibited the best tribological properties having the lowest friction coefficient (0.047), with less frictional force (2.617N), as against the mineral oil ISO VG6 conventionally used for lubricating turbine bearings with coefficient of friction (0.051) and frictional force (2.862N), this improved tribological properties were as a result of the additives blend in the development of the bio lubricating oil. Among the developed castor oil turbine lubricant, sample (COTL3) have the lowest coefficient of friction (0.058), less frictional force (3.242N) and low wear scar diameter (0.49mm). The study confirms that the modified vegetable oils are suitable, eco-friendly alternatives to mineral-based turbine lubricants with competitive performance with that of mineral oil ISO VG46.